Semantic analysis of different types of discourse in the works by Rumi and Disdar (Eurasian Journal of Philology Science and Education, 2016)
The most outstanding Sufi thinker Mevlana Jalal al-Din Muhammad Rumi (1207, born in 1207 in the city of Balkh, the largest city in the province of Khorasan -1273, Konya, Turkey) and the Bosnian poet Mak Dizdar Mahmedaliya (1917, Stolac, Bosnia and Gertsegovina- 1971 Sarajevo, Bosnia and Herzegovina), separated by seven hundred years and two different languages, seem to be too distant and dissimilar. The first one worked in the Persian language, and the other used the local Bosnian idioms – both seemed to have been working in different, non-tangible ways. However, under similar conditions, these two writers share a common historical background and the same attitude to conciseness of the language. This article is about semantic peculiarities of Rumi and Disdar’s poetry based on different discourses, represented in their works. Various approaches to the one and the same topics are described in relation to symbols and archetypes, and uniqueness of their language.
Keywords: Mevlana Rumi; Mak Dizdar; traditions of sufism; semantic characteristics; discourse analysis; symbols.